Socio-spatial negotiations in Lisbon: Reflections of working-aged lifestyle migrants on place and privilege - Lea Molina Caminero; Jennifer McGarrigle (Population, Space and Place, 2022)
In the context of inequalities inherent in regimes of mobility and the rapid transformation of Lisbon by increased tourism and transnational mobility, this paper seeks to foreground under-the-radar narratives of young working-aged middle-class migrants on their socio-spatial positioning in the city. Situated at the nexus of youth mobilities and lifestyle migration, our objective is to examine the stratifications and diversities present within lifestyle migration to the city by focusing on migration motivations and migrants' own reflections on their place-making strategies and privilege in the city. Based on 10 narrative interviews and participant observation in transnational hangouts, our results reveal how the creation of “alternative” lifestyles is hinged on both mobility practices and local moorings as young movers reinvent themselves professionally in the place of arrival. Our results show that they negotiate their place and social position through (i) balancing place-consumption practices between what is construed as the transnational and the local and (ii) by situating themselves outside of the subjective residential geography of privileged migrants. This is part of a moral code to appease their political conscience and justify their presence in a city that has been rapidly transformed by tourism and other transient populations.
Keywords: 300; mobility regimes; place-consumption; privilege; residential choice; urban change; urban lifestyle migration